2009
DOI: 10.1073/pnas.0811834106
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F elevates blood pressure and promotes atherosclerosis

Abstract: Little is known about prostaglandin F2␣ in cardiovascular homeostasis. Prostaglandin F2␣ dose-dependently elevates blood pressure in WT mice via activation of the F prostanoid (FP) receptor. The FP is expressed in preglomerular arterioles, renal collecting ducts, and the hypothalamus. Deletion of the FP reduces blood pressure, coincident with a reduction in plasma renin concentration, angiotensin, and aldosterone, despite a compensatory upregulation of AT1 receptors and an augmented hypertensive response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
93
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 53 publications
8
93
2
Order By: Relevance
“…Interestingly, the pressor effect of Ang II was potentiated in FP knock-out animals (9) suggesting that basal interactions are important for establishing physiological parameters as for the ghrelin receptor/D2-dopamine receptor pair. We observed asymmetric effects on ligand binding as the presence of AT1R altered the affinity of PGF2␣ for FP but not the converse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the pressor effect of Ang II was potentiated in FP knock-out animals (9) suggesting that basal interactions are important for establishing physiological parameters as for the ghrelin receptor/D2-dopamine receptor pair. We observed asymmetric effects on ligand binding as the presence of AT1R altered the affinity of PGF2␣ for FP but not the converse.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups (including us) have shown that FP activates ERK1/2 in HEK 293 cells via the G␣ q -PKC pathway (5)(6)(7) and that this response was modulated by both biased allosteric and orthosteric ligands (5,8). FP has been shown to be involved in blood pressure regulation by the angiotensin II (Ang II) type 1 receptor (AT1R) (9). AT1R plays a critical role in vascular remodeling and is part of the renin-angiotensin system, a key regulator of blood pressure, electrolyte balance, and numerous neuronal and endocrine actions associated with cardiovascular function.…”
Section: At1r/fp Dimers May Thus Be Important In the Regulation Of Blmentioning
confidence: 99%
“…5,6) Some studies have reported the ability of PGF2α to elevate blood pressure. 7,8) Although some clinical trials have reported that topical PGF2α analogs are safe, [9][10][11] they are thought to cause systemic adverse events. Some examples include ophthalmic timolol or brimonidine, which reduce systemic blood pressure by β-receptor blocking [12][13][14] or α-receptor stimulating actions.…”
mentioning
confidence: 99%
“…1 Now that the receptor has been shown to be involved in the renin-angiotensin system, it offers a new way to attack a pathway that has already yielded multiple marketed drugs.Depression of the renin-angiotensin system (RAS) is known to decrease systemic blood pressure and slow atherogenesis, the formation of atherosclerotic plaques. 2 Although signaling through the prostaglandin E 2 receptor (PTGER4; PGE 2 ) and the prostacyclin receptor (PTGIR; IP; PGI2) is known to modulate this pathway, 3,4 the role of the prostaglandin F receptor (PTGFR; FP) has been less clear.…”
mentioning
confidence: 99%
“…1 Now that the receptor has been shown to be involved in the renin-angiotensin system, it offers a new way to attack a pathway that has already yielded multiple marketed drugs.…”
mentioning
confidence: 99%